MAGNETIC SURVEY IN ONGUL ISLANDS, EAST ANTARCTICA - ノギ, ヨシフミ; セアマ, ノブカズ; イセザキ, ノブヒロ; フナキ, ミノル; NOGI, Yoshifumi; SEAMA, Nobukazu; ISEZAKI, Nobuhiro; FUNAKI, Minoru (National Institute of Polar Research, 1991)
P(論文) Total intensities of the geomagnetic field were measured in the eastern part of West Ongul Island and the southern part of East Ongul Island during the 30th Japanese Antarctic Research Expedition (JARE-30) in 1989. Measurements were carried out along two east-west observation lines in West Ongul Island and two east-west and three north-south observation lines in East Ongul Island. The variations of magnetic anomalies in West Ongul Island seem to correlate with the surface geology, while those in East Ongul Island do not. A model calculation showed a positive correlation of the obtained variations in West Ongul Island with the geological structure and the paleomagnetic results. However, widths and positions of the magnetic anomaly source model are slightly different from those of the surface geological structure. These differences provide information how the surface geological structure extends underground. departmental bulletin paper